Biomechanical effect of tibial slope on the stability of medial unicompartmental knee arthroplasty in posterior cruciate ligament-deficient knees - Lee, Jin-Ah (Bone Joint Res, 2020)
AIMS: Unicompartmental knee arthroplasty (UKA) has become a popular method of treating knee localized osteoarthritis (OA). Additionally, the posterior cruciate ligament (PCL) is essential to maintaining the physiological kinematics and functions of the knee joint. Considering these factors, the purpose of this study was to investigate the biomechanical effects on PCL-deficient knees in medial UKA. METHODS: Computational simulations of five subject-specific models were performed for intact and PCL-deficient UKA with tibial slopes. Anteroposterior (AP) kinematics and contact stresses of the patellofemoral (PF) joint and the articular cartilage were evaluated under the deep-knee-bend condition. RESULTS: As compared to intact UKA, there was no significant difference in AP translation in PCL-deficient UKA with a low flexion angle, but AP translation significantly increased in the PCL-deficient UKA with high flexion angles. Additionally, the increased AP translation became decreased as the posterior tibial slope increased. The contact stress in the PF joint and the articular cartilage significantly increased in the PCL-deficient UKA, as compared to the intact UKA. Additionally, the increased posterior tibial slope resulted in a significant decrease in the contact stress on PF joint but significantly increased the contact stresses on the articular cartilage. CONCLUSION: Our results showed that the posterior stability for low flexion activities in PCL-deficient UKA remained unaffected; however, the posterior stability for high flexion activities was affected. This indicates that a functional PCL is required to ensure normal stability in UKA. Additionally, posterior stability and PF joint may reduce the overall risk of progressive OA by increasing the posterior tibial slope. However, the excessive posterior tibial slope must be avoided. Cite this article: Bone Joint Res 2020;9(9):593–600.